Exploring attitude-behaviour inconsistencies in organic food consumption during the COVID-19 pandemic in the Klang Valley, Malaysia - Cheah, W.K.A.; Aigbogun, Osaro (2022)
Many consumers have shown positive attitude towards green consumption; nevertheless, these attitudes do not necessarily translate into intention and or behaviours. Human consumption patterns are responsible for approximately 40% of environmental challenges; therefore, consumer decisions and behaviours have a big impact on the environment. Food consumption is known to have an important impact on public health, individuals, and the environment. Organic food purchase is widely known to promote sustainable attitudes and lifestyles. The disparity between green concern (having a positive attitude and or intention) and green behaviour (the act of purchasing and consuming organic food) is known as the attitude-behaviour inconsistency or green gap in the scholarly sphere. To explore the attitude-behaviour inconsistency, this study employs exogenous influences such as motives and barriers which extends the original theory of planned behaviour. This qualitative study which was carried out during the COVID-19 pandemic involved 22 key respondents’ residents in the Klang Valley, Malaysia (KVM) using key informant interviews and interpretive phenomenological analysis. The findings indicated motives and barriers to purchase, coexist with a positive attitude (endogenous influence) and favourable intentions, resulting in real behaviour or purchase not being possible; therefore, the attitude-behavioural inconsistencies. To band the attitude-behaviour inconsistency, it is proposed that decision makers such as government agencies create a national environmental certification procedure and logo that verifies companies' environmental claims. Assisting the government, the private sector should be more proactive in implementing green lifestyle initiatives in their corporate policies and when conducting business.